Analysis of Specialty Coffee Business Performances: Focus on Management of Farmer Organizations in Indonesia - Diany Faila Sophia Hartatri; Lya Aklimawati; Jeffrey Neilson (Indonesian Coffee and Cocoa Research Institute, 2019)
Indonesian specialty coffee farmer organization is established by Government of Indonesia (GoI) for managing coffee production, processing, and marketing in farmer group level. Through farm-level industrialization program, the GoI supported coffee farmer organizations in several specialty coffee producing regions for increasing farmers’ livelihoods. These farmer organizations are encouraged to produce higher quality of coffee in term of specialty coffee and link directly with buyers. Therefore, the farmer groups would obtain the profits that can be shared to the members of farmer organizations. This research aims firstly to understand the performances, challenges and risk management of specialty coffee business on farmer organizations level across Indonesia, and secoundly to understand the profits gained by specialty coffee farmer organizations. The research has been conducted in several specialty coffee producing regions, including Bali, East Java, Flores and South Sulawesi. The case study and ethnography were carried out by collecting data through direct observation and in depth interviews. Number of respondents were 27 producer organizations which were selected by judgement sampling method. The data were analyzed by using descriptive method and profit analysis. The research results show that alternative model of value chain interventions (VCIs) is required for improving the profits of specialty coffee business on farmer organizations level and farmers’ livelihoods. Maximization the VCIs to increase the benefits for farmers, the VCIs should be conducted by incorporating both off-farm and on-farm aspects.